2022
DOI: 10.1080/07420528.2022.2139713
|View full text |Cite
|
Sign up to set email alerts
|

U-shaped association between sleep duration with chronic constipation and diarrhea: A population-based study

Abstract: Table S1. The univariate analysis of the chronic constipation/chronic diarrhea covariates. Chronic constipation Chronic diarrhea Characteristics N OR (95% CI) p-value N OR (95% CI) p-value Age categorized, years 0.528 <0.001 ≤20 228 1.00(ref) 211 1.00(ref) 20-60 8736 0.79(0.51 -1.22) 0.278 8694 2.83(1.25 -6.40) 0.012 ≥60 3995 0.77(0.50 -1.21) 0.259 4100 3.94(1.74 -8.93) 0.001 Gender, Female 6321 2.29(2.00 -2.61) <0.001 6242 1.49(1.32 -1.69) <0.001 Ethnicity <0.001 <0.001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous NHANES studies reported a higher prevalence of CD in individuals with diabetes (11.2% vs. 6.0%) ( Sommers et al, 2019 ), depression (15.53% vs. 6.05%) ( Ballou et al, 2019a ), sleeping for <4 h (8.4% vs. 7.6%) ( Wang et al, 2022 ), and obesity (9.8% vs. 4.5%) ( Ballou et al, 2019b ). Given this evidence, it was important to consider the potential impact of single Circs components on CD risk, despite variations in definitions.…”
Section: Discussionmentioning
confidence: 94%
“…Previous NHANES studies reported a higher prevalence of CD in individuals with diabetes (11.2% vs. 6.0%) ( Sommers et al, 2019 ), depression (15.53% vs. 6.05%) ( Ballou et al, 2019a ), sleeping for <4 h (8.4% vs. 7.6%) ( Wang et al, 2022 ), and obesity (9.8% vs. 4.5%) ( Ballou et al, 2019b ). Given this evidence, it was important to consider the potential impact of single Circs components on CD risk, despite variations in definitions.…”
Section: Discussionmentioning
confidence: 94%
“…A strength of the current study is that we had a study population with a relatively large number of patients with type 2 diabetes because of the emerging prevalence of diabetes and an elevated risk of sleep and gastrointestinal disorders associated with diabetes. Furthermore, assessment of the defecation frequency allowed us to examine the association of sleep duration with different aspects of constipation, in addition to the stool form or laxative use, which was assessed in a previous study [ 16 ]. Additionally, a comprehensive multivariable adjustment for confounders, such as lifestyle factors of dietary fiber intake, exercise, and smoking, as well as comorbidities including depressive symptoms, was conducted to determine the association between sleep duration and constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is one of the major gastrointestinal symptoms and has recently attracted attention as a risk factor for CVD [9][10][11]. A cross-sectional analysis from NHANES showed that shorter and longer sleep durations were associated with a higher likelihood of constipation [16], which was defined on the basis of stool form (Bristol Stool Form Scale type) or laxative use. Compared with a sleep duration of 7 hours, a shorter sleep duration was significantly associated with constipation (OR: 1.25 [95% CI 1.03-1.51] for 6 hours, 1.57 [1.25-1.98] for 5 hours, and 1.54 [1.16-2.04] for �4 hours).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…People spend about one-third of their time sleeping [9] . The American Academy of Sleep Medicine (AASM) and the Sleep Research Society (SRS) recommend that the optimal sleep time for adults is 7 hours or more per night [10] .…”
Section: Introductionmentioning
confidence: 99%